2010
DOI: 10.1159/000318571
|View full text |Cite
|
Sign up to set email alerts
|

Preproenkephalin Expression in Peripheral Blood Mononuclear Cells of Acutely Underweight and Recovered Patients with Anorexia Nervosa

Abstract: Background: The prohormone preproenkephalin (ppE) and its derived peptides are involved in leukocyte functioning as well as in the regulation of hunger and satiety. Various abnormalities of the immune and endocrine systems have been described in states of malnutrition such as anorexia nervosa (AN). We hypothesized that ppE expression in AN patients may vary depending on the state of the disorder and the extent of malnutrition. Methods: Expression of ppE mRNA was analysed in peripheral blood mononuclear cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 89 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Janas-Kozik et al (2008) found that a leptin receptor transcript showed statistically significant differences between individuals with AN and controls. Several other investigations compared expression of P-glycoprotein (Storch et al, 2008) and prohormone preproenkephalin (Weiss et al, 2010), failed to find significant differences. Although limited in number, these studies have provided some preliminary information regarding transcriptomic profiling in AN.…”
Section: Introductionmentioning
confidence: 99%
“…Janas-Kozik et al (2008) found that a leptin receptor transcript showed statistically significant differences between individuals with AN and controls. Several other investigations compared expression of P-glycoprotein (Storch et al, 2008) and prohormone preproenkephalin (Weiss et al, 2010), failed to find significant differences. Although limited in number, these studies have provided some preliminary information regarding transcriptomic profiling in AN.…”
Section: Introductionmentioning
confidence: 99%
“…Kahl et al observed an increase in TNF-α and IL-6 expression in AN at hospital admission time compared with controls, and TNF-α remained significantly higher while IL-6 expression decreased in weight-restored patients (Kahl et al, 2004). In studies on expression of P-glycoprotein (Storch et al, 2008) and prohormone preproenkephalin (ppE mRNA) (Weiss et al, 2010), neither study could identify evidence to support a significant difference between AN and healthy controls, although ppE mRNA level was negatively associated with depressive and anxious symptoms (Weiss et al, 2010). …”
Section: Alteration Of Gene Expression: Mrna and Methylationmentioning
confidence: 99%
“…Recent studies have revealed that gene expression in peripheral blood cells (PBCs) could be useful for the diagnosis and monitoring of disease activity in psychiatric disorders, such as anorexia nervosa, depression and migraine [21][22][23]. However, the expression of genes that relate to sleep disorders has not been identified.…”
Section: Introductionmentioning
confidence: 99%